The Role of Farmer Groups in Improving the Welfare of Corn Farmers in Tanjung Seteko Village, Indralaya District, Ogan Ilir Regency - sulastri, merna ayu (Sriwijaya Journal of Agribusiness and Biometrics in Agriculture Research, 2023)
Farmer groups are groups of farmers who are bound informally and are formed on the basis of similarity, interests, similar environmental conditions (social, economic, resources), familiarity and harmony, and have leaders to achieve common goals. Farmer groups are formed by and for farmers, in order to overcome common problems in farming and to strengthen farmers' bargaining efforts, both in the market for inputs and in the market for agricultural products. Corn is a staple food and has the potential to become a strategic commodity that plays a significant role in increasing income. The purposes of this study were (1) to assess the role of farmer groups in Tanjung Seteko Village, Indralaya District, Ogan Ilir Regency, (2) to calculate the level of income and welfare of corn farmers in Tanjung Seteko Village, Indralaya District, Ogan Ilir Regency, (3 to analyze the role relationship farmer groups with the level of welfare of corn farmers in Tanjung Seteko Village, Indralaya District, Ogan Ilir Regency. Data collection was carried out from March to April 2023. The method used was survey and observation methods. The sampling method in this study was a simple random method. The results showed that the role of corn farmer groups in Tanjung Seteko Village is moderate or moderate.The average income of corn farmers in Tanjung Seteko Village is IDR 24,108,739/ha in a year.Based on the results of research, the income of corn farmers in Tanjung Seteko Village is higher than the value of the poverty rate in South Sumatra and 70.00% of farmers are in a prosperous level. Based on statistical tests, there is a significant relationship between the role of farmer group variables and the level of welfare with a correlation coefficient value of 0.548.